2017
DOI: 10.1002/jcla.22282
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a panel of serum amino acids for the identification of early chronic kidney disease patients

Abstract: Our data suggest that serum amino acid levels may supply important information for the early detection of chronic kidney disease. We are the first to establish a diagnostic model utilizing serum levels of multiple amino acids for the diagnosis of patients with early-stage chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…High levels of serum phenylalanine were observed in the low-risk and high-risk patients compared with the healthy controls, which suggested that phenylalanine may be a potential biomarker for IgA.N. Li et al ( 70 ) reported high levels of serum phenylalanine in patients with renal function impairment; it was suggested that serum amino acid levels may be used for the early detection of CKD. Contradictory to these results, Li et al ( 71 ) detected low levels of serum phenylalanine in patients with lupus nephritis and idiopathic nephrotic syndrome using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum phenylalanine were observed in the low-risk and high-risk patients compared with the healthy controls, which suggested that phenylalanine may be a potential biomarker for IgA.N. Li et al ( 70 ) reported high levels of serum phenylalanine in patients with renal function impairment; it was suggested that serum amino acid levels may be used for the early detection of CKD. Contradictory to these results, Li et al ( 71 ) detected low levels of serum phenylalanine in patients with lupus nephritis and idiopathic nephrotic syndrome using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Serum cystatin C has been proposed as a simple, accurate, and rapid endogenous marker of GFR in research and clinical practice. 12 However, there are conflicting reports regarding the superiority of Cyst C over serum creatinine, with many studies suggesting significant.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies suggested the important roles of specific plasmafree amino acids (PFAAs) in the development and progression of a wide variety of human diseases [9,10]. Additionally, there is an increasing number of research works assessing the utility of PFAAs as potential disease biomarkers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%